Analysis of Solid Waste Management Scenarios in India: A Comparative Case Study of Indore and Varanasi with Special Emphasis on Policy Gaps and Interventions - Rathore D.; Dubey R.; Singh R.S.; Dwivedi A. (My University, 2025)
Varanasi, the spiritual capital of India, is prominent in the country. It drastically improved its waste management capacity after 2014, when it became the constituency of the prime minister of India. At the same time, Indore established itself as a role model for sanitation in general and solid waste management in particular by securing the title of the cleanest city in India for the fifth consecutive year. Solid waste management is the biggest challenge in India, and it is growing continuously. A comparison between Indore and Varanasi will reveal the gaps in solid waste management in India's two-tier towns. Comparative data analysis of the solid waste composition, chemical composition, cleaning, collection, transportation, treatment, and disposal facilities will provide insight into the shortcomings of waste management. Analysing waste generation in different states and cities with varying population densities will reveal the patterns responsible for better or worse waste management in specific areas. We have analysed data and recognised patterns of waste generation with regard to economic prosperity. This study analyses the policy framework for waste and sanitation in India in comparison to the global context. Many successful policy frameworks are designed by international organisations like the United Nations Environment Programme (UNEP), the United Nations Economic Commission for Europe (UNECE) and the World Bank. We have compared the Indian waste management policy and status with the World Bank's policy framework, as it is the most comprehensive policy framework currently available. We have primarily focused on Indore and compared it with Varanasi regarding policy frameworks and enforcement strategies. This study identifies potential gaps by analysing patterns in waste management and proposes improved ideas for waste-related policies and sustainable development. © 2025 Rathore et al. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.